The rain of years : Great expectations and the world of Dickens - Schilling, Bernard Nicholas (University of Rochester Press, 2001)
This compact survey of all Dickens's novels shows the unity of the whole body of work by reviewing basic scenes and images in the novels. The book argues that Great Expectations is the novel which brings together the main themes of Dickens's vision.